Out-of-autoclave prepreg consolidation under deficient pressure conditions. (July 2014) - Centea, T; Hubert, P
The present study investigated the effects of three pressure-related process deviations (reduced ambient pressure, reduced vacuum and restricted air evacuation) on the consolidation and quality of flat laminates manufactured by out-of-autoclave prepreg processing. The evolution of laminate thickness, measured in-situ, was correlated with thickness and porosity data for woven and unidirectional fibre bed composites. The process deficiencies are shown to have had distinctive detrimental effects on the rate of thickness change and on the amount, distribution and morphology of voids, and to have been more pronounced for the woven fabric prepreg format due to its higher initial bulk factor.